PERANCANGAN EVALUASI PRODUKTIVITAS KERJA KARYAWAN DENGAN METODE SISTEM PENILAIAN KINERJA TERINTEGRASI (IPMS) DAN ANALYTICAL HIERARCHY PROCESS (AHP) DALAM PENGAMBILAN KEPUTUSAN DI UD. BIMASAKTI TIMUR RAYA SURABAYA - Hariyanto, Krisnadhi; Dewi, Fitriya Gemala; Putra, Giovanni Firmansyah; Bima, Putu (Journal of Industrial Engineering and Technology, 2024)
UD. Bimasakti Timur Raya Surabaya, there is an issue of delays in starting work caused by employees not beginning their tasks on time and believing that these delays will not affect their salary or other benefits. The Integrated Performance Measurement System (IPMS) of UD. Bima Sakti Timur Raya focuses solely on financial and sales KPIs, without involving other elements such as internal business processes and development aspects. The percentage of achievement and realization of employee potential improvements in profit enhancement shows a high variation and meets the established target of 15.20%. UD. Bima Sakti Timur Raya demonstrates performance changes by using the Integrated Performance Measurement System (IPMS) and has so far succeeded in meeting the predetermined target of 15.20%. UD. Bima Sakti Timur Raya has successfully achieved its goals, but this effort has still not been able to meet the set target for reducing customer complaints. UD. Bima Sakti Timur Raya experiences inconsistent changes every year, and the company still has not been able to achieve the set targets. UD. Bima Sakti Timur Raya shows growth each year, but the company has yet to meet the established goals.